The detrimental impact of persistent vs an isolated occurrence of de novo donor‐specific antibodies on intermediate‐term renal transplant outcomes. Issue 8 (4th July 2017) - Loucks‐DeVos, Jennifer M.; Eagar, Todd N.; Gaber, A. Osama; Patel, Samir J.; Teeter, Larry D.; Graviss, Edward A.; Knight, Richard J.
Abstract: Background: De novo donor‐specific antibodies (dnDSA) after renal transplant are associated with acute rejection (AR) and graft loss, yet most recipients with dnDSA have stable function and no AR. We assessed whether the persistence of dnDSA increased the risk of a detrimental outcome. Methods: A single‐center review of renal transplant recipients monitored for dnDSA at multiple time points post‐transplant. An Isolated dnDSA was defined as one positive dnDSA and no additional positive tests, whereas ≥2 positive dnDSA was defined as persistent dnDSA. Results: Of 708 recipients, 22% developed dnDSA, of whom 64% had persistent dnDSA. At median follow‐up of 35 (range 12‐74) months, there were fewer episodes of AR in the isolated dnDSA vs the persistent dnDSA group (2% vs 22%; P <.001, ) and fewer graft losses with isolated dnDSA vs persistent dnDSA (0% vs 10%; P =.03). Within the persistent dnDSA group, recipients with dnDSA ≥60% of time points, had more AR (32% vs 16%, P =.10) and more graft losses (21% vs 2%; P =.003) than those with dnDSA<60%. Conclusions: Persistence of dnDSA resulted in more AR and graft failure than a single positive value. Recipients with longer duration of dnDSA persistence had an additional increased risk of AR and graft failure.